Synthesis, characterization, and application of a new methylenethiol resins for heavy metal ions removal. Issue 15 (1st November 2016) - Podkościelna, Beata; Kołodyńska, Dorota; Hubicki, Zbigniew; Gawdzik, Barbara; Bartnicki, Andrzej
ABSTRACT: Polymeric matrices in the form of microspheres were obtained by copolymerization of the tetrafunctional monomers: 2, 3-(2-hydroxy-3-methacryloyloxypropoxy)naphthalene (2, 3-NAF.DM) or (bis[4(2-hydroxy-3-methacryloyloxypropoxy)phenyl]sulphide (BES.DM) with styrene (St). Next multistage modification which introduced the methylenethiol groups on the surface of copolymers was carried out. New materials were used in sorption processes to remove toxic heavy metal ions particularly Cd(II), Pb(II), Cu(II), Zn(II), and Ni(II) from aqueous solutions. The effects of the contact time on the sorption of the above-mentioned ions are presented. Sorption capacity depending on the type of monomers, modification, surface character, and porous structure of polymer was determined. The synthesized microspheres 2, 3-NAF.DM-St-CH2 SH and BES.DM-St-CH2 SH indicate potential to adsorb heavy metal ions in the state and batch equilibrium systems.